Property Price Attributable to Subdivision Neighbourhood Designs: Hedonic Pricing Model Approach in Bangkok Metropolitan Region, Thailand (International Journal of Built Environment and Sustainability, 2020)
The purpose of this paper is to determine whether the property price is caused by the subdivision neighbourhood designs in the Bangkok Metropolitan Region (BMR), Thailand. A total price model is developed during the analysis process. The model provides a greater understanding of the significance of the subdivision neighbourhood designs that are related to property pricing. This paper is based on data collection from 50 subdivisions across the BMR area. The hedonic pricing approach is used to develop the models. The semi-log models are developed on 1,182 samples of property sales located in eight zones of the BMR. The independent variables include general bundles of property characteristics and the subdivision neighbourhood design items. There are two major findings in this study. First, this study provides a suitable property price model for subdivision development in the BMR. The model presents the high level of R2 at 0.948. The model confirms that all classical hedonic variables are statistically significant to the property price. Furthermore, the additional alternative variables for the subdivision neighbourhood design items can improve the level of variation explained by the model. Second, this study finds that the average property price attributable to the subdivision neighbourhood design is about 20.24 % of the total property price. The components of the subdivision neighbourhood design items consist of project characteristics, recreation features, social facilities, and transportation system design. The model should support knowledge of the design’s impact on the property price for the Government or policy makers on making appropriate policies for urban and environmental management. The model provides a guideline for developers on appropriate property selling-prices for subdivision development in the BMR. The new understanding of the property price attributable to the subdivision neighbourhood designs support suitable decision making on new subdivision development in the BMR
Keywords: Property price; Subdivision neighbourhood designs; Single-family house; Hedonic pricing; Bangkok Metropolitan Region